The Evolution of Islamic Thought Paradigms in Indonesia: A Comparative Analysis of Modernist, Traditionalist, and Liberal Perspectives - Saifudien Djazuli; Rifqi (Penerbit Hellow Pustaka, 2025)
This study explores the diverse landscape of Islamic thought in Indonesia through the perspectives of prominent intellectuals. Ahmad Syafi'i Ma'arif categorizes Islamic thought into four distinct paradigms: modernism (evolving into neo-modernism), neo-traditionalism, exclusive Islam, and Muslim secular-modernism. Similarly, M. Dawam Raharjo identifies four styles: Muslim nationalism, humanism, Muslim socialist-secularism, and secular-modernism. Within this discourse, Nurcholish Madjid posits that modernization is inherently synonymous with rationalization. This conceptual framework originates from the liberalization of thought, which seeks to reform traditional cognitive patterns and non-rational (non-aqliyah) procedures into rational (aqliyah) systems. Furthermore, the emergence of Liberal Islam represents a contemporary milestone in Indonesian Islamic discourse. Driven by a dynamic generation of intellectuals, this movement integrates critical modern scholarship to reshape the existing worldview. Liberal Islam proactively challenges regressive cultural and intellectual trends, offering a transformative